Nafkah Istri Nushūz Perspektif Imam Syafi’i dan Ibn Hazm - Khoironi, Riadina; Muhsin, Muhsin (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
Livelihood is one of the important things in human life, so it is necessary to study it. However, there are differences of opinion about the livelihood of Nushuz's wife. This study examines more deeply the livelihood of the wife of Nushuz by focusing on two problem formulations, namely 1) the livelihood of the wife of Nushuz according to the opinion of Imam Shafi'i and Ibn Hazm, and 2) the legal istinbat used by Imam Shafi'i and Ibn Hazm looking at the issue of livelihood. For nushuz's wife. Using a qualitative literature research method, this research concludes that according to Imam Syafi'i, a nushuz's wife is not entitled to her husband's maintenance until she quits her nushuz. Meanwhile, according to Ibn Hazm, whether the wife of Nushuz or not, she is still entitled to a living from her husband. The legal istinbat used by Imam Shafi'i is qiyas, while Ibn Hazm is the explicit meaning of the Qur'an letter an-Nisa verse 34.